Broadband mm‐wave propagation characterization of planar groove gap waveguide. Issue 5 (11th January 2020) - Oyedokun, Titus; Geschke, Riana H.; Stander, Tinus
Abstract: We present, experimental broadband propagation characterization of a planar groove gap waveguide (PGGWG) from 29 to 40 GHz. The transmission line Q‐factor is found to vary from 110 to 130 over the band, which is shown by comparison of measurement data to be comparable to substrate integrated waveguide (SIW). PGGWG is found to have a phase constant of nearly double that of SIW using the same materials and manufacturing process. This is a significant result for system miniaturization.